Enteric Hepatitis: A case report - Nepal, A; Acharya, R; Ojha, AR; Sah, S (Journal of Kathmandu Medical College, 2013)
Enteric fever is a common cause of morbidity and hospital admission in developing countries. This can sometimes be complicated by rare complications like hepatitis. One should be careful when selecting antibiotics like ceftriaxone in such children which can cause biliary stasis. Our case of enteric hepatitis treated with ceftriaxone developed a prolonged jaundice with biliary stasis as a result of antibiotic therapy. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8147 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 103-105